THE EFFECT OF A DIBLOCK COPOLYMER COMPATIBILIZER ON THE INTERFACE BETWEEN IMMISCIBLE POLYMERS - Bucknall, D; Higgins, J; Penfold, J (1992)
Neutron critical reflection and small angle scattering (SANS) have been used to study the effect of a symmetric diblock copolymer poly(styrene-block-methyl methacrylate) added to blends of the immiscible homopolymers of polystyrene and poly(methyl methacrylate). © 1992.